Study on the consolidation behavior of horizontal drainage foundation under complex aquifer formation conditions in karst regions - Xu, Yunbo; Zhang, Jiachao; Liu, Zhongyu; Cui, Penglu (Frontiers in Earth Science, 2023)
Introduction: The consolidation behavior of horizontal drainage foundation under complex aquifer conditions in karst areas is a hot topic in the field of geotechnical engineering. Methods: This paper presents a modified piecewise-linear model for plane-strain consolidation. In this model, the distributed drainage boundary was used to describe the drainage performance of soil layer boundaries, and the UH model considering the time effect was selected to reflect soil’s rheological property. Through comparison with existing research, the validity of the calculation model in this paper was verified. Then several examples were used to analyze the consolidation behavior of the foundation under the combined action of rheological effect and distributed drainage boundaries. Results and discussion: Numerical studies show that the phenomenon of the increase of excess pore pressure exists in the foundation of the distributed drainage boundary after considering the rheology in the early stage of consolidation. Moreover, the larger the secondary consolidation coefficient and the initial over-consolidation parameter, or the smaller the pave rate and the thickness-width ratio, the above phenomenon is more obvious. In terms of the dissipation of the pore water pressure, the larger the secondary consolidation coefficient and the initial over-consolidation parameter, the slower the pore pressure dissipation, and the smaller the pave rate or the thickness-width ratio can achieve the above effects. In terms of the impact on settlement, the above-mentioned parameters are consistent, that is, the larger the corresponding parameter, the larger the corresponding settlement value.